ADSORPSI LOGAM BERAT OLEH KARBON AKTIF BAMBU SCHIZOSTACHYUM DI AIR TANAH BALIKPAPAN - Samosir, Harrys; Michael Alexander Hutabarat; Devina Sanchia Samosir (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
Water pollution caused by industrial activities, particularly by heavy metals and non-biodegradable dyes, has become an increasingly serious issue. Adsorption using activated carbon is an effective, economical, and simple solution. Local bamboo such as Schizostachyum sp. from Balikpapan holds potential as a sustainable and low-cost raw material for activated carbon. This study examines the optimal production parameters by analyzing the material properties and adsorption performance. The methods used include the carbonization and activation of Schizostachyum sp. bamboo, crystal structure characterization using X-ray Diffraction (XRD), surface morphology analysis using Scanning Electron Microscopy (SEM), and the evaluation of heavy metal adsorption efficiency using Atomic Absorption Spectroscopy (AAS). The results showed a very high adsorption efficiency, with lead and cadmium removal exceeding 97%, demonstrating its potential as a non-toxic adsorbent.